A case report: the use of ultrasound guided peripheral nerve block during above knee amputation in a severely cardiovascular compromised patient who required continuous anticoagulation. Issue 9 (March 2018) - Karm, Myong-Hwan; Lee, Sohee; Yoon, Syn-Hae; Lee, Sukyung; Koh, Wonuk
Abstract: Rationale: Although lower–extremity surgeries are mainly performed under general or central neuraxial anesthesia, ultrasound-guided peripheral nerve block (PNB) can be a good alternative, especially for patients who require continuous anticoagulation treatment and present with poor cardiovascular conditions. Patients concerns: The patient required continuous anticoagulation treatment due to the high risk of thromboembolism and poor cardiovascular conditions. Diagnoses: The patient required lower-extremity amputation due to atherosclerotic and thromboembolic obstruction. Interventions: We decided to progress the operation under peripheral nerve block. The sciatic, femoral, lateral femoral cutaneous nerve and anterior branch of the obturator nerve were blocked under ultrasound guidance. Sixty ml of a local anesthetic (equal mix of 1% lidocaine and 0.375% ropivacaine) was administered for the block. Outcomes: Sufficient sensory block at the area of amputation was obtained, and the patient's vital signs were stable throughout surgery. Lessons: Ultrasound-guided peripheral nerve block can be an excellent anesthetic technique for patients receiving radical surgery at the proximal lower extremities, especially patients who are critically ill and considered high risk.